Minimization of total harmonic distortion and enhancing voltage level for hybrid multilevel converter with different sources - Veerendra, A. S.; Mohd Rusllim, Mohamed; Peddakapu, K.; Sekhar, Chavali Punya (John Wiley & Sons, Inc., 2020)
In order to improve the voltage levels and reducing the total harmonic distortions (THDs), a symmetrical hybrid multilevel converter (MLC) topology with different sources, that is, a photovoltaic (PV) source and a constant DC source for electric drive applications are proposed in this article. The presented topology comprises of distinctive converters for each phase, is coupled to a 3∅ asynchronous motor. The two converters are operated with low voltage, high frequency, and high voltage, which are fundamental to increase the output voltage. A modified phase‐shifted pulse width modulation technique helps to control the power of semiconductor devices. The reduced component count and THD of the hybrid MLC are assessed using the conventional topologies. It was found that the THD is 15.10% in voltage and 1.97% in current for the proposed system and exhibits better performance in relative to the PV source. Finally, the simulation outcomes accompanied by comparative analysis are also discussed in the article.